The color of plant reproduction: macroecological trade-offs between biotic signaling and abiotic tolerance - Burns, Kevin C. (Frontiers in Ecology and Evolution, 2015)
Flowers and fruits are often vividly colored. An obvious explanation for fruit and flower pigmentation is that it serves to attract animal mutualists. However, decades of research has produced equivocal support for the hypothesis that animals are the primary selection pressure acting on the color of plant reproductive structures. Exciting new research into geographic variation in flower colors suggests an alternative explanation—flower pigments protect gametes against the damaging effects of solar radiation. Here, I present new evidence suggesting that a similar explanation might apply to Rubus spectabilis, a much studied but poorly understood bird-dispersed plant species. These and other recent results provide a new perspective on the color of plant reproduction. In addition to signaling to animals, fruit, and flower colors might often play vital roles in protecting plants against the harmful effects of solar radiation.